Composite hydrogel with photothermal effect and preparation method and application thereof
By wrapping the photothermal hydrogel on natural bacterial cellulose to form a composite hydrogel with a skin core structure, the inelastic and non-adhesion problems of bacterial cellulose dressing are solved, and local overheating of the wound is avoided in photothermal treatment, achieving safer and more effective wound repair.
Patent Information
- Application Number
- CN202311275209.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The prior art is difficult to maintain the natural structure of bacterial cellulose and functionalize it, resulting in the inability to fix the bacterial cellulose as a dressing to the wound, and hydrogels with adhesion and photothermal properties are prone to local overheating of the wound during photothermal treatment, causing secondary damage.
The composite hydrogel with a skin core structure is used to mold the photothermal hydrogel around the surrounding surface of natural bacterial cellulose and wrap it with natural bacterial cellulose. After freezing-thawing, the three-dimensional network structure of natural bacterial cellulose is maintained, and has good elasticity and tensile properties.
The problem of inelasticity and adhesion of natural bacterial cellulose when used as dressing is solved, the secondary damage when changing the dressing in wounds is improved, and the temperature at the wound surface is balanced and adjusted during laser irradiation to avoid the problem of local high temperature.
Smart Images

Figure CN119701072A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite hydrogels, and more specifically, relates to a composite hydrogel with photothermal effect and a preparation method and application thereof. Background Art
[0002] Hydrogel is a type of extremely hydrophilic three-dimensional network structure gel that can swell in water and retain a large amount of water without dissolving. Therefore, a large number of hydrogels are used in facial masks and wound dressings.
[0003] Bacterial cellulose (BC) is a nano-sized cellulose secreted by Acetobacter xylinum during its production and movement. Compared with other celluloses, BC has been widely studied and applied in biomedical fields, such as wound repair, artificial blood vessels, drug sustained-release carriers and neural interfaces, due to its high water holding capacity, low immunogenicity, good biocompatibility and mechanical properties. Especially in the field of wound repair, BC is an excellent material for facial masks and wound dressings due to its high water holding capacity. However, many functional modifications of BC currently require that natural bacterial cellulose (nBC) be dissolved and then functional materials be added to give it corresponding functions, and then a cross-linking agent be added to obtain regenerated bacterial cellulose (rBC), so that rBC obtains various functions and properties, but the rBC obtained by this method loses the three-dimensional network structure and certain mechanical properties of nBC, and loses the advantages of nBC. In addition, natural bacterial cellulose is not sticky and cannot adhere to and fix around the wound surface, which limits its application as a dressing.
[0004] A composite material with adhesive properties is prepared together with bacterial cellulose, so that the composite material with bacterial cellulose adheres and fixes around the wound surface. For example, polydopamine (PDA) has good adhesive and photothermal properties and is widely used in the preparation of various adhesive hydrogels and photothermal hydrogels. However, the adhesive hydrogel is in direct contact with the wound surface and may tear the wound surface when changing the dressing. At the same time, when using ordinary single hydrogels with photothermal effect, although it has the effect of promoting the proliferation of fibroblasts and vascular cells, the temperature of ordinary photothermal hydrogels is the highest in the middle during photothermal treatment, or the long laser irradiation time causes the hydrogel to lose water and thus the temperature is unstable, resulting in local overheating of the wound surface, causing secondary injuries such as bleeding and inflammation of the wound surface.
[0005] In summary, how to maintain the natural structure of bacterial cellulose and functionalize it, solve the problem that natural bacterial cellulose cannot be fixed on the wound surface as a dressing, and solve the problem of secondary damage to the wound by hydrogels with adhesive and photothermal properties are issues that technical personnel in this field urgently need to solve. Summary of the invention
[0006] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a composite hydrogel with photothermal effect, and a preparation method and application thereof. The composite hydrogel with photothermal effect provided by the present invention is a skin-core structure, which is formed by surrounding the natural bacterial cellulose with a photothermal hydrogel and wrapping the natural bacterial cellulose. The composite hydrogel can maintain the three-dimensional network structure of natural bacterial cellulose after freezing and thawing, and has good elasticity and tensile properties, which solves the problem of inelasticity and non-adhesion of natural bacterial cellulose when used as a dressing. The composite hydrogel provided by the present invention can be applied to skin wound repair, so that it can improve the secondary damage to the wound caused by the process of changing the wound dressing, and balance and adjust the temperature at the wound during laser irradiation, without the problem of local high temperature.
[0007] In a first aspect of the present invention, a composite hydrogel with photothermal effect is provided. The composite hydrogel is a skin-core structure, comprising natural bacterial cellulose and photothermal water gel; wherein the natural bacterial cellulose is a core layer, and the photothermal water gel is a skin layer.
[0008] As a preferred embodiment of the present invention, the natural bacterial cellulose is in a swelling equilibrium state.
[0009] As a preferred embodiment of the present invention, the thickness of the natural bacterial cellulose and the photothermal water gel are both 1 to 10 mm, preferably 3 mm.
[0010] As a preferred embodiment of the present invention, the photothermal water gel comprises polydopamine, polyvinyl alcohol and water; wherein the water content of the photothermal water gel is 87.5-95wt%; the mass fraction of the polyvinyl alcohol in the photothermal water gel is 5-12.5wt%; and the polydopamine is prepared by oxidation of dopamine hydrochloride under alkaline conditions.
[0011] As a preferred embodiment of the present invention, the photothermal water gel comprises bacterial cellulose, bamboo charcoal and water, the mass volume ratio of the bacterial cellulose to water is 15g / L to 30g / L, and the mass volume ratio of the bamboo charcoal to water is 0.5g / L to 1g / L.
[0012] In a second aspect of the present invention, a method for preparing a composite hydrogel having a photothermal effect is provided, comprising the following steps:
[0013] S11: placing natural bacterial cellulose in deionized water to reach swelling equilibrium, cutting it into a predetermined shape, and placing it at the center of the bottom of the mold;
[0014] S12: Weigh dopamine hydrochloride and dissolve it in deionized water, adjust the pH to 8.0-8.8, and obtain a polydopamine solution; weigh polyvinyl alcohol powder and add it to the polydopamine solution, mix well, and adjust the pH to neutral to obtain a photothermal water gel solution;
[0015] S13: evenly distributing the photothermal water gel solution around the natural bacterial cellulose in the mold of step S11, freezing it at -10 to -80°C for 8 to 12 hours, and then melting it to obtain a composite hydrogel.
[0016] As a preferred embodiment of the present invention, the concentration of dopamine hydrochloride is 0.019 g / L to 0.285 g / L.
[0017] In a third aspect of the present invention, a method for preparing a composite hydrogel having a photothermal effect is provided, comprising the following steps:
[0018] S21: placing natural bacterial cellulose in deionized water to reach swelling equilibrium, cutting it into a predetermined shape, and placing it at the center of the bottom of the mold;
[0019] S22: lithium hydroxide: urea: deionized water are weighed in a weight ratio of 4.6:15:80.4 and fully dissolved to obtain a bacterial cellulose solvent; bacterial cellulose is weighed separately to make a homogenate, and dried to form a bacterial cellulose powder; the bacterial cellulose powder and bamboo charcoal are dissolved in a solvent, mixed in an ice bath, and placed in an environment of -10°C to fully dissolve to obtain a photothermal water gel solution;
[0020] S23: adding glutaraldehyde to the photothermal water gel solution, mixing evenly, and then evenly arranging the solution around the natural bacterial cellulose in the mold in step S11, and leaving the solution at room temperature to obtain a composite hydrogel.
[0021] In a fourth aspect of the present invention, there is provided use of the composite hydrogel with photothermal effect as described in any one of the first aspects of the present invention for preparing a wound dressing or a drug release carrier.
[0022] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0023] (1) The composite hydrogel provided in the embodiment of the present invention is a skin-core structure, wherein the natural bacterial cellulose is the core layer, and the photothermal water gel is the skin layer. The composite hydrogel can also maintain the three-dimensional network structure of the natural bacterial cellulose after freezing and thawing, and has significantly improved elasticity and tensile properties relative to pure bacterial cellulose. Therefore, when the composite hydrogel of the present invention is used as a wound dressing, since the core layer of the natural bacterial cellulose of the composite hydrogel has no adhesion properties, the problem of tearing damage to the wound caused by the wound during the dressing change process can be improved; and since the natural bacterial cellulose is wrapped by the photothermal water gel, and the natural bacterial cellulose has no photothermal properties, the problem of local high temperature in the center during laser irradiation can be improved.
[0024] (2) The natural bacterial cellulose in the embodiments of the present invention is a biomaterial with excellent biocompatibility and very low immunogenicity. A variety of cells can grow on it and it can inhibit the proliferation of scars. In addition, natural bacterial cellulose can absorb pus from the wound due to its good water retention, reduce inflammatory response, and reduce the chance of infection. Moreover, natural bacterial cellulose has no photothermal properties. During laser irradiation, the temperature of the composite hydrogel can be adjusted to maintain a suitable temperature of the wound part in contact with the natural bacterial cellulose, thereby preventing adverse reactions caused by overheating of the wound. In addition to the above advantages, natural bacterial cellulose also has the advantage of not adhering to the wound, thus preventing secondary damage when changing the dressing.
[0025] (3) In the embodiment of the present invention, when the photothermal water gel is composed of dopamine and polyvinyl alcohol, PVA, as a material with good biocompatibility, has good elasticity and tensile properties. The PVA solution is converted into a PVA hydrogel with good elasticity and skin-friendliness through a "freeze-thaw" method without adding a cross-linking agent; dopamine hydrochloride generates polydopamine in an alkaline environment, and polydopamine makes the PVA hydrogel have adhesion and photothermal properties. Under the irradiation of laser, the peripheral PVA part of the composite hydrogel is heated, and the normal skin around the wound is stimulated to promote wound repair.
[0026] When polyvinyl alcohol is combined with polydopamine, the outer surface of the resulting composite hydrogel has the dual properties of adhesion and photothermal, and has good elasticity and tensile properties, while the interior retains the characteristics of natural bacterial cellulose. When polyvinyl alcohol and polydopamine are preferably used as the photothermal hydrogel part of the composite hydrogel, the composite hydrogel can be fixed around the wound surface without adhering to the wound during wound repair, and can also reduce the temperature of the center of the composite hydrogel and the wound surface, preventing problems such as excessive local temperature at the wound surface during photothermal treatment.
[0027] (4) In the embodiments of the present invention, the concentration of dopamine hydrochloride is preferably 0.019 g / L to 0.285 g / L. For example, the concentration of dopamine hydrochloride is 0 g / L (0 mmol), 0.095 g / L (0.5 mmol), 0.190 g / L (1 mmol) or 0.285 g / L (1.5 mmol). As the concentration of dopamine hydrochloride is higher, the amount of polydopamine generated under alkaline conditions is higher, so that the photothermal conversion efficiency is higher and the viscosity is also greater. Different concentrations can be selected as required to meet the needs as a thermotherapy for skin wounds. Preferably, 0.5 mmol has a suitable temperature and is not too hot. The difference in temperature rise between 1 mmol and 1.5 mmol after being used in a "composite" hydrogel is not as great as that between 0-0.5 mmol and 0.5-1 mmol.
[0028] (5) In the embodiments of the present invention, when the photothermal water gel is composed of bacterial cellulose and bamboo charcoal, firstly, the regenerated bacterial cellulose has some advantages that the natural bacterial cellulose does not have. The texture of the natural bacterial cellulose is dense, and many other materials and substances cannot be mixed into the interior. However, after the bacterial cellulose is dissolved, it can be mixed with other materials very evenly, and then re-crosslinked by a cross-linking agent to generate regenerated natural bacterial cellulose, the bacterial cellulose is functionalized, and the regenerated bacterial cellulose can obtain the desired functional properties; secondly, the bamboo charcoal has a good photothermal conversion ability, and the nano-scale bamboo charcoal particles can be very evenly dispersed inside the cellulose, and the material properties are stable.
[0029] When regenerated bacterial cellulose and bamboo charcoal constitute the photothermal hydrogel, the bamboo charcoal particles are evenly compounded in the bacterial cellulose solution, and the cross-linking at room temperature better maintains the effect of natural bacterial cellulose. In addition, the composite hydrogel has photothermal properties, which can convert not only near-infrared light energy into thermal energy, but also far-infrared, and has lower requirements for instruments in photothermal applications.
[0030] (6) In the embodiment of the present invention, the photothermal water gel is formed around the natural bacterial cellulose and the natural bacterial cellulose is wrapped to form a composite hydrogel with photothermal effect. Without using any crosslinking agent, PVA and BC are crosslinked together by physical crosslinking method, and the obtained hydrogel can be used without washing, and there is no need to worry about the potential harm of crosslinking agent residue.
[0031] (7) In the embodiments of the present invention, when the composite hydrogel is used as a wound dressing, it can significantly improve the secondary damage to the wound during the dressing change, and the problem of local high temperature on the wound surface will not occur during the laser irradiation process. At the same time, the composite hydrogel of the present invention can maintain the characteristics of the internal natural bacterial cellulose, and based on the structure of the external photothermal water gel, the photothermal performance of the composite hydrogel is a uniform and suitable mild temperature during wound repair.
[0032] For example, it has obvious effects on the healing of both acute and chronic wounds. By comparing the recovery of acute wounds and chronic wounds, the photothermal properties of the photothermal water gel part of the composite hydrogel play a very obvious effect in the recovery of acute wounds; while the natural bacterial cellulose part also plays an important role in the recovery process of chronic wounds, which may be related to the fact that the inflammation process of chronic wounds lasts longer and there is more pus, and the advantage of natural bacterial cellulose that it can fully absorb pus. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram of the structure of a composite hydrogel according to an embodiment of the present invention;
[0034] Figure 2 This is a UV-vis test graph of the photothermal water gel solution of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 1 of the present invention;
[0035] Figure 3 is a scanning electron microscope image of a cross section of a natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 2 of the present invention, Figure 3 i in the figure is a cross-sectional scanning electron micrograph of a natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel; Figure 3 ii in the figure is the electron microscopy image of the photothermal water gel; Figure 3 Figure iii is an electron micrograph of the junction between natural bacterial cellulose and photothermal water gel; Figure 3 Figure iv is an electron microscope image of natural bacterial cellulose;
[0036] Figure 4 This is a mechanical property characterization diagram of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 3 of the present invention; Figure 4 Figure a shows the compression, stretching, and knotted stretching properties of the photothermal water gel in turn; Figure 4 b shows the initial state (origin), horizontal stretch (horizontal stretch) and four-side stretch (four-side stretch) performance of the composite hydrogel; Figure 4 c in the figure shows the stretching and twisting properties of the composite hydrogel; Figure 4 d in is the stress-strain curve of the composite hydrogel; Figure 4 Eg in the figure are the mechanical properties data diagrams of the composite hydrogel, such as the maximum strain, maximum deformation and Young's modulus;
[0037] Figure 5This is a graph showing the adhesion performance of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 4 of the present invention; Figure 5 Figure a is a diagram showing the adhesion of the photothermal water gel on the surface of skin, pig liver, pig fat and pig muscle. Figure 5 b is the adhesion test data of the photothermal water gel; Figure 5 c in the figure is a diagram showing the adhesion of the composite hydrogel on the surfaces of glass, steel, polytetrafluoroethylene (PTFE) and skin.
[0038] Figure 6 This is a characterization diagram of the photothermal performance of the photothermal water gel of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 5 of the present invention; Figure 6 a in the figure is the infrared thermal imaging image of the photothermal water gel with different DA concentrations and different irradiation time; Figure 6 b in the figure is the statistical diagram of the maximum temperature data of the photothermal water gel with different DA concentrations and different irradiation time;
[0039] Figure 7 This is a photothermal performance characterization diagram of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 5 of the present invention; Figure 7 a in the figure is the infrared thermal imaging image of the composite hydrogel with different DA concentrations irradiated for different time periods; Figure 7 b is a statistical diagram of the maximum temperature of composite hydrogels containing different DA concentrations irradiated at different times; Figure 7 c is a photothermal performance data diagram of the composite hydrogel with DA concentration in Example 2 at different base plate temperatures; Figure 7 d in the figure is the photothermal performance data of the composite hydrogel with DA concentration in Example 2 under different irradiation intensities; Figure 7 e in the figure is the experimental data of laser irradiation cycle;
[0040] Figure 8 The figure is a result of the biocompatibility and blood compatibility of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 6 of the present invention; Figure 8 a in the figure shows the live-dead cell staining of NIH3T3 cells and HUVEC cells on natural bacterial cellulose using Calcein-AM / PI; Figure 8 b is the biocompatibility experiment of natural bacterial cellulose and photothermal hydrogels with different concentrations of DA in natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel; Figure 8 Figure c is the blood compatibility experiment of natural bacterial cellulose and photothermal water gel with different concentrations of DA in natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel;
[0041] Fig. 9 This is a graph showing the results of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 7 of the present invention on the acute wound surface of SD rats; Fig. 9 a in the figure is the acute wound healing diagram of different experimental groups; Fig. 9 b is a statistical chart of the relative wound area of each experimental group at different time points;
[0042] Fig.10 The RT-PCR results of the inflammatory factor-related genes of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel on the wound surface of SD rats on the 14th day corresponding to Test Example 7 of the present invention;
[0043] Fig.11 This is a result diagram of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 8 of the present invention on the chronic wound surface of type I diabetic rats; Fig.11 a in the figure is the healing picture of diabetic wounds in different experimental groups; Fig.11 b in the figure is the wound healing trajectory diagram; Fig.11 c in the figure is a statistical chart of the relative wound area of each experimental group at different time points;
[0044] Fig.12 The expression level of IL-1β in diabetic wounds of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 8 of the present invention; Fig.12 a in the figure is the immunofluorescence image of IL-1β-labeled and CD68-labeled macrophages in diabetic wounds of different experimental groups on days 3 and 7; Fig.12 b in the figure is the percentage of IL-1β-positive macrophages to CD68-positive macrophages; Fig.12 c in the figure is the relative gene expression of IL-1β in diabetic wounds of different experimental groups on days 3, 7, and 14;
[0045] Fig.13 The results of IL-6 expression level of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel on diabetic wound surface corresponding to Test Example 8 of the present invention; Fig.13 a in the figure is the immunofluorescence image of IL-6 expression level in diabetic wounds of different experimental groups on the 3rd day; Fig.13 b in the figure is the relative gene expression of IL-6 in diabetic wounds of different experimental groups on days 3, 7, and 14;
[0046] Fig.14 This is a picture of pus near the wound when the wound surface of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 8 of the present invention was replaced in the early stage of the diabetic wound of the rat;
[0047] Fig.15The expression level of IL-10 in diabetic wounds of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 8 of the present invention; Fig.15 a in the figure is the immunofluorescence image of IL-10 expression level in diabetic wounds of different experimental groups on the 3rd day; Fig.15 b in the figure is the IL-10 positive coverage rate of diabetic wounds in different experimental groups;
[0048] Fig.16 CD206 fluorescence immunographs of diabetic wound surfaces of each group of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogels corresponding to Test Example 8 of the present invention;
[0049] Fig.17 The H&E staining and granulation thickness statistics of each group of diabetic wounds of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 9 of the present invention; Fig.17 a in the figure is the HE staining picture of diabetic wounds in different experimental groups; Fig.17 b in the figure is the thickness of granulation tissue on the diabetic wound surface in different experimental groups;
[0050] Fig.18 The graphs showing the results of epidermal growth on the diabetic wound surfaces of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogels corresponding to Test Example 9 of the present invention; Fig.18 a in the figure is the CK14 staining image of diabetic wounds in different experimental groups; Fig.18 b in the figure is the relative expression of KGF in diabetic wound tissues of different experimental groups;
[0051] Fig.19 Masson staining and collagen deposition percentage statistics of each group of diabetic wounds of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 10 of the present invention; Fig.19 a in the figure is the Masson staining image of the diabetic wound surface in each group; Fig.19 b in the figure is a statistical chart of the percentage of collagen deposition in the diabetic wounds of each group;
[0052] Fig. 20 Statistical graphs of CD34 immunohistochemical staining and positive coverage of each group of diabetic wounds of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Test Example 10 of the present invention; Fig. 20 a in the figure is the CD34 immunohistochemistry image of diabetic wounds in each group; Fig. 20 b in the figure is the positive rate of CD34 staining in the same field of view.
[0053] Description of the drawings: The marks or legends in the drawings are specifically described as follows: Mark: 1 is a composite hydrogel with photothermal effect, 2 is natural bacterial cellulose, and 3 is a photothermal water gel. Legend: "Yang" is a photothermal water gel; "Yin" is a natural bacterial cellulose; "Tai-Chi" is a natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel; "Control" is 3M Tegaderm TM "Tai-Chi-NIR" is a commercial dressing of "Tai-Chi-NIR Film"; "PC" is a positive control group; "NC" is a negative control group. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0055] like Figure 1 As shown, the composite hydrogel 1 with photothermal effect includes natural bacterial cellulose 2 and photothermal water gel 3; wherein the natural bacterial cellulose 2 is located inside the composite hydrogel 1, and the photothermal water gel 3 is evenly distributed on the periphery of the natural bacterial cellulose 2 to form a composite hydrogel with a skin-core structure.
[0056] In the embodiment of the present invention, the photothermal water gel 3 is a hydrogel with photothermal function and the photothermal water gel 3 uniformly wraps the natural bacterial cellulose 2 .
[0057] Among them, the thickness of natural bacterial cellulose and photothermal water gel is between 1 and 10 mm, and the thickness of natural bacterial cellulose 2 is required not to collapse after melting due to being too high. Preferably, the thickness of natural bacterial cellulose and photothermal water gel is the same, and is 3 mm. Among them, the thickness of photothermal water gel is the distance of photothermal water gel along the direction of natural bacterial cellulose; the thickness of natural bacterial cellulose is consistent with the thickness direction of photothermal water gel. For example, the composite hydrogel finally formed is used in the form of sheets or thin blocks, and the composite hydrogel is attached to the area to be healed as a dressing or a carrier for drug release, so that the central area of the surface attached to the area to be healed is natural bacterial cellulose, and is in direct contact with the area to be healed, and the periphery is photothermal water gel.
[0058] In the embodiments of the present invention, the natural bacterial cellulose is in a swelling equilibrium state.
[0059] In an embodiment of the present invention, the photothermal water gel is formed by dopamine and polyvinyl alcohol, and the water content of the photothermal water gel is 87.5-95wt%, specifically, polydopamine particles are uniformly dispersed in a PVA solution, and then the PVA is frozen and cross-linked to form. Or, the photothermal water gel is formed by bacterial cellulose and bamboo charcoal. Specifically, bamboo charcoal is dispersed in a bacterial cellulose solution, and natural bacterial cellulose is dissolved to form a bacterial cellulose solution, and the solution is cross-linked to form regenerated natural bacterial cellulose.
[0060] The polyvinyl alcohol is polyvinyl alcohol 1750±50, 99% hydrolysis degree, and the mass fraction of the polyvinyl alcohol in the photothermal water gel is 5-12.5wt%; the polydopamine is prepared by oxidizing the polydopamine with dopamine hydrochloride under alkaline conditions.
[0061] In an embodiment of the present invention, a method for preparing a composite hydrogel with photothermal effect is provided, wherein the hydrogel comprises the following components: natural bacterial cellulose, photothermal water gel and water, and the specific preparation process is as follows:
[0062] 1) Place natural bacterial cellulose in deionized water to reach swelling equilibrium, cut into a desired shape, and place in the center of the bottom of a desired mold for later use. For example, the mold is a twelve-well plate or a six-well plate or a disposable plate.
[0063] 2) Dissolve dopamine hydrochloride with a concentration of 0 to 1.5 mmol in deionized water, adjust the pH to between 8.0 and 8.8 with 0.1 mol / L NaOH, and stir the mixture with a magnetic stirrer at 800 rpm for 30 minutes to obtain a uniform polydopamine solution for later use.
[0064] 3) The weighed polyvinyl alcohol powder is added to the polydopamine solution of step 2), for example, stirred in a 90° C. water bath for 2 hours, and then the pH is adjusted to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution.
[0065] 4) The photothermal water gel in step 3) is evenly coated or injected around the natural bacterial cellulose in step 1), and then frozen at -10°C to -80°C for 8 to 12 hours, and then melted to obtain a composite hydrogel.
[0066] When the photothermal water gel is composed of bacterial cellulose, bamboo charcoal and water, the specific preparation process is as follows:
[0067] 1) placing natural bacterial cellulose in deionized water to reach swelling equilibrium, cutting it into a desired shape, and placing it at the center of the bottom of a desired mold for later use;
[0068] 2) Weigh lithium hydroxide: urea: water in a weight ratio of 4.6:15:80.4 in a beaker, fully dissolve to obtain a bacterial cellulose solvent, and store at 4°C for later use;
[0069] 3) weighing natural bacterial cellulose and slurrying it, drying it to form bacterial cellulose powder; weighing 1.5% bacterial cellulose powder and 0.1% bamboo charcoal in a bacterial cellulose solvent, stirring for 2 hours in an ice bath, and then placing it at -10°C to fully dissolve the bacterial cellulose, thereby obtaining a bacterial cellulose solution;
[0070] 4) Add 72 μL of glutaraldehyde to every 100 g of the bacterial cellulose solution in step 3), stir quickly and evenly, then evenly apply it around the natural bacterial cellulose and leave it at room temperature for 24 hours to obtain a composite hydrogel with photothermal effect.
[0071] 5) Soaking the composite hydrogel in step 4) in deionized water to remove excess glutaraldehyde crosslinking agent for subsequent experiments.
[0072] The specific embodiments are as follows:
[0073] Example 1
[0074] Natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, specifically as follows:
[0075] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the bottom center of a six-hole plate mold for standby use;
[0076] 2) dissolving 0 mmol dopamine hydrochloride (DA) in deionized water, adjusting the pH to 8.5 with 0.1 mol / L NaOH, and stirring with a magnetic force of 800 rpm for 30 minutes to obtain a polydopamine solution for later use;
[0077] 3) weighing 10% (w / w) polyvinyl alcohol powder into the polydopamine solution of step 2), stirring in a 90° C. water bath for 2 hours, and then adjusting the pH to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution;
[0078] 4) The photothermal water gel solution in step 3) is evenly coated on the four sides of the natural bacterial cellulose in step 1), and placed in a -20°C refrigerator to freeze overnight. After thawing the next day, a composite hydrogel with photothermal effect is obtained.
[0079] Example 2
[0080] Natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, specifically as follows:
[0081] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the center of the bottom of a six-well plate mold for later use;
[0082] 2) dissolving 0.5 mmol dopamine hydrochloride (DA) in deionized water, adjusting the pH to 8.5 with 0.1 mol / L NaOH, and stirring with a magnetic force at 800 rpm for 30 minutes to obtain a polydopamine solution for later use;
[0083] 3) weighing 10% (w / w) of the polyvinyl alcohol powder into the polydopamine solution of step 2), stirring in a 90° C. water bath for 2 hours, and then adjusting the pH to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution;
[0084] 4) The photothermal water gel solution in step 3) is evenly coated on the four sides of the natural bacterial cellulose in step 1), and placed in a -20°C refrigerator to freeze overnight. After thawing the next day, a composite hydrogel with photothermal effect is obtained.
[0085] Example 3
[0086] Natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, specifically as follows:
[0087] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the center of the bottom of a six-well plate mold for later use;
[0088] 2) dissolving 1 mmol dopamine hydrochloride (DA) in deionized water, adjusting the pH to 8.5 with 0.1 mol / L NaOH, and stirring with a magnetic force at 800 rpm for 30 minutes to obtain a polydopamine solution for later use;
[0089] 3) weighing 10% (w / w) of the polyvinyl alcohol powder into the polydopamine solution of step 2), stirring in a 90° C. water bath for 2 hours, and then adjusting the pH to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution;
[0090] 4) The photothermal water gel solution in step 3) is evenly coated on the four sides of the natural bacterial cellulose in step 1), and placed in a -20°C refrigerator to freeze overnight. After thawing the next day, a composite hydrogel with photothermal effect is obtained.
[0091] Example 4
[0092] Natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, specifically as follows:
[0093] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the center of the bottom of a six-well plate mold for later use;
[0094] 2) dissolving 1.5 mmol dopamine hydrochloride (DA) in deionized water, adjusting the pH to 8.5 with 0.1 mol / L NaOH, and stirring with a magnetic force at 800 rpm for 30 minutes to obtain a polydopamine solution for later use;
[0095] 3) weighing 10% (w / w) of the polyvinyl alcohol powder into the polydopamine solution of step 2), stirring in a 90° C. water bath for 2 hours, and then adjusting the pH to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution;
[0096] 4) The photothermal water gel solution in step 3) is evenly coated on the four sides of the natural bacterial cellulose in step 1), and placed in a -20°C refrigerator to freeze overnight. After thawing the next day, a composite hydrogel with photothermal effect is obtained.
[0097] Example 5
[0098] Natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, specifically as follows:
[0099] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the center of the bottom of a six-well plate mold for later use;
[0100] 2) dissolving 1.5 mmol dopamine hydrochloride (DA) in deionized water, adjusting the pH to 8.5 with 0.1 mol / L NaOH, and stirring with a magnetic force at 800 rpm for 30 minutes to obtain a polydopamine solution for later use;
[0101] 3) weighing 5% (w / w) of the polyvinyl alcohol powder into the polydopamine solution of step 2), stirring in a 90° C. water bath for 2 hours, and then adjusting the pH to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution;
[0102] 4) The photothermal water gel solution in step 3) is evenly coated on the four sides of the natural bacterial cellulose in step 1), and placed in a -20°C refrigerator to freeze overnight. After thawing the next day, a composite hydrogel with photothermal effect is obtained.
[0103] Example 6
[0104] Natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, specifically as follows:
[0105] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the bottom center of a six-well plate mold for later use;
[0106] 2) dissolving 1.5 mmol dopamine hydrochloride (DA) in deionized water, adjusting the pH to 8.5 with 0.1 mol / L NaOH, and stirring with a magnetic force at 800 rpm for 30 minutes to obtain a polydopamine solution for later use;
[0107] 3) weighing 7.5% (w / w) of the polyvinyl alcohol powder into the polydopamine solution of step 2), stirring in a 90° C. water bath for 2 hours, and then adjusting the pH to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution;
[0108] 4) The photothermal water gel solution in step 3) is evenly coated on the four sides of the natural bacterial cellulose in step 1), and placed in a -20°C refrigerator to freeze overnight. After thawing the next day, a composite hydrogel with photothermal effect is obtained.
[0109] Example 7
[0110] Natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, specifically as follows:
[0111] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the center of the bottom of a six-well plate mold for later use;
[0112] 2) dissolving 1.5 mmol dopamine hydrochloride (DA) in deionized water, adjusting the pH to 8.5 with 0.1 mol / L NaOH, and stirring with a magnetic force at 800 rpm for 30 minutes to obtain a polydopamine solution for later use;
[0113] 3) weighing 12.5% (w / w) of the polyvinyl alcohol powder into the polydopamine solution of step 2), stirring in a 90° C. water bath for 2 hours, and then adjusting the pH to neutral with 1% HCl (v / v) to obtain a photothermal water gel solution;
[0114] 4) The photothermal water gel solution in step 3) is evenly coated on the four sides of the natural bacterial cellulose in step 1), and placed in a -20°C refrigerator to freeze overnight. After thawing the next day, a composite hydrogel with photothermal effect is obtained.
[0115] The above embodiments 1-7 are only examples. The content parameters of polydopamine can also be adjusted according to actual conditions. In addition to the above examples of 0.095 g / L, 0.190 g / L and 0.285 g / L, in actual experiments, the polydopamine prepared when the concentration of dopamine hydrochloride is ensured to be 0.019 g / L to 0.285 g / L can be used to prepare photothermal water gel, which can achieve photothermal effect and be applied to the composite hydrogel of the present invention, and realize the corresponding technology.
[0116] Example 8
[0117] Natural bacterial cellulose-bacterial cellulose / bamboo charcoal composite hydrogel, specifically as follows:
[0118] 1) After the natural bacterial cellulose is subjected to swelling equilibrium, it is cut into a desired shape and placed at the center of the bottom of a six-well plate mold for standby use;
[0119] 2) Weigh lithium hydroxide: urea: water in a weight ratio of 4.6:15:80.4 in a beaker, fully dissolve to obtain a bacterial cellulose solvent, and store at 4°C for later use;
[0120] 3) Weighing 1.5% of the bacterial cellulose powder in step 1) and 0.1% of bamboo charcoal into a bacterial cellulose solvent, stirring in an ice bath for 2 hours, and then placing at -10°C to fully dissolve the bacterial cellulose, thereby obtaining a bacterial cellulose solution;
[0121] 4) adding 72 μL of glutaraldehyde to every 100 g of the bacterial cellulose solution in step 3), stirring rapidly and evenly, then evenly coating around the natural bacterial cellulose, and leaving at room temperature for 24 hours to obtain a hydrogel with photothermal effect;
[0122] 5) Soaking the hydrogel in step 4) in deionized water to remove excess glutaraldehyde crosslinking agent for subsequent experiments.
[0123] The above-mentioned embodiment 8 is only an example, and the content parameters of bamboo charcoal can also be adjusted according to actual conditions. In actual experiments, the amount of bamboo charcoal added is guaranteed to refer to the existing technology, for example, the mass volume ratio of bacterial cellulose to water is 15g / L to 30g / L, and the mass volume ratio of bamboo charcoal to water is 0.5g / L to 1g / L. Composite hydrogels with photothermal effect can be prepared, and photothermal effect can be achieved, and applied to the composite hydrogel of the present invention, and the corresponding technology can be achieved.
[0124] The composite hydrogel in the embodiment of the present invention was prepared by the above method and adjusting the ratio of different raw materials. In the composite hydrogel in the above Examples 1-8, natural bacterial cellulose was cut into a circle with a diameter of 1.4 cm to obtain natural bacterial cellulose, which was placed at the center of the bottom of the same six-well plate mold, thereby controlling the thickness of the natural bacterial cellulose and the photothermal water gel to be 3 mm.
[0125] The following are test examples of the above embodiments, specifically:
[0126] Test Example 1, UV-vis test experiment of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel based on Examples 1-4, specifically as follows:
[0127] Based on the successful oxidation polymerization of DA into PVA solution in Examples 1-4 to form a precursor solution for photothermal water gel formation, the photothermal water gel solutions with different DA contents were diluted 4 times and their absorption peaks were tested by UV-vis. Figure 2It can be seen that with the addition of DA, the precursor solution of photothermal hydrogel formation has an obvious absorption peak at 320nm, and the absorption peak increases with the increase of DA concentration. This absorption peak is the π-π* transition of aromatic hydrocarbons containing benzene ring structure, proving that DA is successfully oxidized and polymerized in the precursor solution of photothermal hydrogel formation.
[0128] Test Example 2, based on the scanning electron microscopy test of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel of Example 2, wherein the details are as follows:
[0129] The hydrogel in Example 2 was freeze-dried, and then the cross-section of the hydrogel was tested by field emission scanning microscopy. Figure 3 The results show that after freezing and cross-linking, there is a clear and obvious boundary line between the photothermal hydrogel part and the natural bacterial cellulose. The partial network of the photothermal hydrogel at the junction penetrates into the network structure of the natural bacterial cellulose, while there is no network structure of the photothermal hydrogel in the natural bacterial cellulose at the far end. Therefore, it is shown that the composite hydrogel of the present invention well maintains the three-dimensional spatial structure of natural bacterial cellulose and maintains the natural structure of bacterial cellulose.
[0130] Test Example 3, based on the mechanical properties experiments of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, photothermal water gel and natural bacterial cellulose corresponding to Examples 1-4, is as follows:
[0131] The composite hydrogels in Examples 1-4 were deformed to different degrees. Figure 4 As shown in a, the photothermal hydrogel exhibits good compression, stretching, and knotting properties. Subsequently, we subjected the composite hydrogel to different degrees of deformation, such as Figure 4 As shown in Figures b and c, the composite hydrogel can be stretched horizontally, stretched on four sides, and twisted well. During the stretching process, the photothermal hydrogel part is stretched longer than the natural bacterial cellulose part and has better deformation and elasticity. Figure 4 The dg in the figure is a mechanical property test, and the test conditions are 50% relative humidity and a tensile rate of 30 mm / min. The results show that the elongation at break of the photothermal water gel is above 200%, and the Young's modulus is 23.88±2.20 KPa-29.00±3.68 KPa, while the elongation at break of natural bacterial cellulose is only 27.93±5.27%, and the Young's modulus is 5.54±1.68 MPa. The above results illustrate the difference in mechanical properties between the inner and outer parts of the composite hydrogel of the present invention. The natural bacterial cellulose has high strength but poor tensile properties, while the photothermal water gel has better tensile properties but weaker strength. The strong tensile properties of the photothermal water gel can better adapt to the process of skin stretching.
[0132] Test Example 4, based on the adhesion performance experiment of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Examples 1-4, is as follows:
[0133] The photothermal water gels in Examples 1-4 were tested for their adhesion properties on several tissue surfaces, including skin, pig liver, pig fat, and pig muscle. Figure 5 As shown in Fig. b, the adhesion strength of the photothermal gel increases with the increase of DA concentration, indicating that DA can improve the viscosity of the photothermal gel. Figure 5 As can be seen from c in FIG, the composite hydrogel can adhere to different materials, including glass, steel, polytetrafluoroethylene (PTFE) and skin. The above indicates that the incorporation and oxidative polymerization of DA can provide viscosity for the composite hydrogel of the present invention, and has the potential to be used as a wound dressing.
[0134] Test Example 5, based on the photothermal performance experiment of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Examples 1-4, is as follows:
[0135] A constant temperature plate was used to simulate the human skin temperature (32°C), and the radiation condition was 808nm laser (near-infrared, NIR) with an irradiation intensity of 1W / cm -2 The irradiation time was 30 minutes, and the temperature was tested every 5 minutes with an infrared temperature gun. Figure 6 As shown in the figure, the addition of DA can increase the temperature of the photothermal hydrogel, and the temperature increases with the increase of DA concentration, and the highest temperature is concentrated in the middle part. After 10 minutes, the temperature is too high, causing the water in the hydrogel to evaporate, resulting in the subsequent continuous increase in temperature and insufficient temperature stability. Under the same experimental conditions, Figure 7 As shown in a, the composite hydrogel can reduce the temperature of the peripheral photothermal hydrogel because the natural bacterial cellulose does not have photothermal properties, thereby improving the temperature stability of the hydrogel within 20 minutes. When used as a wound dressing, it can directly contact the wound to prevent local overheating and damage to the wound. Figure 7 b in the figure is the statistical value of the highest temperature of the composite hydrogels containing different DA concentrations. It can be seen that the 0.5 mmol composite hydrogel has strong stability under NIR irradiation, reaching 41.13±0.31°C after 5 minutes of irradiation, and the temperature is 41.17±0.23°C after 20 minutes. The temperature is the most stable and the temperature range is appropriate, which meets the needs of the next experiment.
[0136] Since the temperature of the skin in different parts is different, we simulated the surface temperature of the skin in different parts through a constant temperature plate. The skin temperature of rats is higher than that of humans. The average skin temperature of rats tested by an infrared detector was around 34°C, so we chose 32°C, 34°C and 37°C to test the changes in the photothermal effect. The results are as follows Figure 7 As shown in Figure c, the photothermal conversion capacity is related to the bottom skin temperature. The higher the bottom temperature, the higher the temperature of the hydrogel. In order to achieve the most suitable temperature for animal experiments (40-41°C), we set the constant temperature plate at 34°C and adjusted the irradiation intensity to 0.8, 0.9 and 1 W / cm -2 , the results are as follows Figure 7 As shown in d, 0.9W / cm -2 The temperature was the most suitable, so the subsequent animal experiments selected 0.5mmol composite hydrogel and 0.9W / cm -2 In addition, in order to test the thermal stability of the composite hydrogel, we conducted three “on-off” laser irradiation cycle experiments on the photothermal stability of 0.5 mmol composite hydrogel, such as Figure 7 As shown in Fig. e, the composite hydrogel exhibits very good thermal stability.
[0137] Verify that the dopamine hydrochloride in Examples 1-4 is oxidatively polymerized into PVA to prepare a wound dressing with photothermal properties, and solve the problem of improving the temperature stability of the composite hydrogel and solving the problem of possible overheating in the central part.
[0138] Test Example 6, based on the biocompatibility and blood compatibility experiments of the natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Examples 1-4, is as follows:
[0139] The cell stability experiments were conducted on the natural bacterial cellulose part and the photothermal hydrogel part of the hydrogel of the present invention. NIH3T3 and HUVEC cells were used to simulate fibroblasts and vascular cells respectively. Since the natural bacterial cellulose is in direct contact with the wound surface, the live and dead cells on the surface of the natural bacterial cellulose were detected by the Calcein-AM / PI double staining method. Calcein-AM stains live cells, and the cells are green, while PI stains dead cells, and the cells are red. Figure 8 As shown in a, NIH3T3 cells and HUVEC cells were inoculated on natural bacterial cellulose for 1 day, and the cells adhered to and grew on the natural bacterial cellulose. After 3 days of culture, both cell types continued to grow, and there were not many dead cells, indicating that direct contact is good for cell survival.
[0140] In order to further verify the effects of natural bacterial cellulose and photothermal water gel on cell activity, CCK-8 was used to test the effects of photothermal water gel and natural bacterial cellulose extracts containing different DA concentrations on cells. Figure 8 Figure b shows that compared with the PC group, the cell viability of each group was above 80% on the 1st and 3rd days, indicating that the biocompatibility of the composite hydrogel of the present invention is very good. In addition, the blood compatibility of the natural bacterial cellulose and the photothermal water gel of the hydrogel of the present invention was evaluated. Figure 8 The c in Figure 3 shows that the hemolysis rate of each group is below 5%, indicating that the composite hydrogel has good blood compatibility. In summary, it is shown that the present invention has good biosafety and can be used for the next in vivo experiment.
[0141] Test Example 7, based on the acute full-thickness cortical injury experiment of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel of Examples 1-4, is as follows:
[0142] The acute full-thickness skin injury mold of SD (Sprague Dawley) rats was selected for the experiment. After the rats were fed adaptively, they were anesthetized by intraperitoneal injection of 1% sodium pentobarbital (30 mg / kg), hair was removed, and a full-thickness skin injury wound with a diameter of 1 cm was made. The experiment was divided into three groups, among which the control group was 3M Tegaderm TM Film is a commercial dressing, Tai-Chi is a natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel, and Tai-Chi-NIR is a natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel assisted with near-infrared light 808nm irradiation. The Tai-Chi-NIR group was irradiated for 20 minutes every day from day 1 to day 5. Photos were taken on days 3, 7, 10, and 14, and samples were collected on days 7 and 14.
[0143] from Fig. 9 As can be seen from a in the figure, compared with the other two groups, the wound healing speed of the Tai-Chi-NIR group was significantly improved, and the wound was completely closed on the tenth day. Fig. 9 In b, we can see the statistics of the relative area of the wound surface. The wound surface of the Tai-Chi-NIR group is significantly smaller than that of the Control group and the Tai-Chi group, while there is no significant difference between the Tai-Chi group and the Control group. This shows that in the healing process of acute wounds, the level of wound healing of Tai-Chi hydrogel alone is not much different from that of commercial dressings. Its effect of accelerating wound healing is mainly due to its photothermal properties, indicating that the warm effect promotes the repair of acute wounds. Next, we used RT-PCR technology to detect inflammatory factors in the new tissue of the wound surface on the 14th day. Fig.10It can be seen that Tai-Chi hydrogel alone can significantly downregulate the levels of proinflammatory factors IL-6 and TNF-α and increase the level of anti-inflammatory factor IL-10, while Tai-Chi hydrogel synergistic with NIR stimulation can significantly downregulate the level of proinflammatory factor IL-1β and further increase the level of proinflammatory factor IL-10. Moreover, the effect on IL-1β is only related to the photothermal effect, and has little to do with Tai-Chi hydrogel itself, while the effect on IL-6 level is only related to Tai-Chi hydrogel itself, and has little to do with the photothermal effect, which suggests that Yin affects IL-6 and IL-10, and photothermal affects IL-1β and IL-10. This result suggests that Tai-Chi hydrogel may be more suitable as a chronic wound dressing.
[0144] Test Example 8, based on the diabetic chronic full-thickness cortical injury experiment of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel of Examples 1-4, is as follows:
[0145] The diabetic chronic full-thickness cortical injury model of SD (Sprague Dawley) rats was selected for the experiment. After the rats were adaptively fed, they were fasted but not watered for 12-18 hours in advance, and then intraperitoneally injected with 60 mg / kg of streptozocin (STZ). Within one week after the injection, the blood sugar of the rats was randomly tested. If the blood sugar of the rats exceeded 16.7 mmol / L three times, the type I diabetes model was successfully established. Subsequently, the other experimental steps were consistent with test example 7, and samples were collected on the 3rd, 7th, and 14th days.
[0146] Depend on Fig.11 As can be seen from a in the figure, unlike acute wounds, the effect is most obvious on the third day before wound healing. Compared with the Control group, the Tai-Chi hydrogel alone has the effect of promoting wound healing, and the Tai-Chi-NIR group with synergistic NIR stimulation has a further promoting effect. Fig.11 b in the figure is the wound healing trajectory diagram of a. Fig.11 Figure c shows the statistical results. During the entire healing process, there were significant differences among the Tai-Chi group, Tai-Chi-NIR group and Control group, while the significant differences between the Tai-Chi-NIR and Tai-Chi groups were mainly on the 3rd and 7th days, with little effect on later time points.
[0147] Simple composite hydrogel and composite hydrogel combined with NIR treatment can change the inflammatory microenvironment of diabetic wounds, as follows:
[0148] The above experiments show that the effect of Tai-Chi hydrogel on diabetic wounds is mainly on the 3rd and 7th days, especially on the 3rd day. This period is mainly the inflammatory stage of the wound. Fig.12Figure a is the co-staining image of IL-1β and CD68 (macrophage marker), and figure b is the percentage of IL-1β and CD68 fluorescence intensity on the third day of figure a. It can be seen that the downregulation of IL-1β level is mainly affected by NIR, and Fig.12 The RT-PCR results of the whole process in c showed the same results. Compared with the Control group and Tai-Chi group, the IL-1β level in the Tai-Chi-NIR group was downregulated, which suggested that the photothermal hydrogel of Tai-Chi hydrogel mainly affected IL-1β. Fig.13 Figure a shows that on the third day, the IL-6 positive rates in the Tai-Chi group and Tai-Chi-NIR group were lower than those in the Control group, while there was little difference between the Tai-Chi group and the Tai-Chi-NIR group. Fig.13 The gene expression results of b in show the same results. Fig.14 It shows that in the first few days of the wound healing cycle, when we changed the dressing, the wounds of the Tai-Chi group and Tai-Chi-NIR group were dry, while the Control group accumulated a lot of pus. IL-6 is an indicator related to sepsis. This suggests that the pus adsorption function of Yin hydrogel in Tai-Chi hydrogel is an important reason for the downregulation of its IL-6 index. In addition, we also detected the changes in the level of the anti-inflammatory factor IL-10. Fig.15 Figure a shows that on day 3, the level of IL-10 was highest in the Tai-Chi-NIR group, followed by the Tai-Chi group, and lowest in the Control group. Fig.15 The b shows Fig.15 The positive rate of IL-10 in the Tai-Chi-NIR group was significantly higher than that in the other two groups. These results confirmed the hypothesis of Test Example 7 that Tai-Chi hydrogel has the function of regulating the wound microenvironment, and this beneficial effect is more obvious in chronic wounds with longer inflammatory periods. Fig.16 As shown, we marked the wound tissue with CD206 (a marker of M2 macrophages). It can be seen that the CD206 level in the Tai-Chi-NIR group on the third day was significantly higher than that in the other two groups, and the Tai-Chi group was also higher than the Control group. This indicates that in diabetic wounds, Tai-Chi hydrogel can promote the transformation of macrophages to M2, and this effect can be greatly enhanced under the stimulation of NIR, promoting the wound to enter the proliferation phase.
[0149] Test Example 9, based on the experiment of promoting granulation and epidermal formation on diabetic wounds of natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Examples 1-4, is as follows:
[0150] In order to further explore the effect of Tai-Chi hydrogel on the formation of granulation tissue and epidermal tissue in diabetic wounds of rats, the wound tissue was characterized by H&E staining and CK14 (Cytokeratin 14, a keratinocyte marker) immunohistochemical staining. Fig.17 From a, we can see that the new tissue generation in the Tai-Chi-NIR group is faster than that in the other two groups. On the 14th day, mature hair follicles (red arrows) and glands (yellow arrows) have been formed. On the 3rd day, we can also see that the granulation tissue grows faster than that in the other two groups. Fig.17 As can be seen in b, on the 3rd day, the thickness of granulation tissue in the Tai-Chi-NIR group was significantly higher than that in the Tai-Chi group and the Control group, while that in the Tai-Chi group was also significantly higher than that in the Control group. Fig.18 It can also be seen in a that the level of CK14 in the Tai-Chi-NIR group (blue arrow) was significantly higher than that in the other two groups, and a complete epidermis was formed on the 7th day. Fig.18 Figure b is the RT-PCR result of KGF (Keratinocyte growth factor). The same results can be seen. On the third day, the expression of KGF in the Tai-Chi-NIR group was significantly higher than that in the other two groups. In addition, Fig.17 and Fig.18 The results showed that compared with the Control, the Tai-Chi hydrogel alone also promoted epidermal growth.
[0151] Test Example 10, based on the experiment of promoting collagen and angiogenesis in diabetic wounds by using natural bacterial cellulose-polyvinyl alcohol / polydopamine composite hydrogel corresponding to Examples 1-4, is as follows:
[0152] Collagen production and angiogenesis are important indicators for evaluating wound repair. In order to further explore the effect of Tai-Chi hydrogel on collagen production and angiogenesis in diabetic wounds of rats, Masson staining and CD34 (vascular endothelial cell marker) immunohistochemical staining of wound tissue were used for characterization. Fig.19 As shown in a, the collagen production in the Tai-Chi-NIR group was faster than that in the other two groups. On the 14th day, the collagen deposition effect of the wound surface in this group was not much different from that of the surrounding normal tissues. Fig.19 The statistical data of b also show that the amount of collagen deposition in the Tai-Chi-NIR group was significantly higher than that in the other two groups on days 3, 7, and 14. Blood vessels provide nutrients for wound formation. Fig. 20CD34 in a shows the generation of vascular endothelial cells in the wound tissue. It can be seen that as the wound healing process progresses, in the middle and late stages, the blood vessels (purple arrows) gradually disappear and their diameters gradually decrease. The blood vessel diameters in the Tai-Chi-NIR group on the 7th and 14th days are significantly smaller than those in the other two groups. Fig. 20 The b statistics also show that in the early stage of wound healing, the proportion of blood vessels in the Tai-Chi-NIR group was significantly higher than that in the other two groups, providing nutrition for wound repair. As wound healing accelerated, on the 14th day, the amount of blood vessels in this group was significantly lower than that in the other two groups, indicating that the wound repair process was faster. The above results show that the Tai-Chi hydrogel of the present invention can promote wound repair, and the stimulation of synergistic NIR can greatly increase angiogenesis and collagen deposition, indicating that the photothermal effect of the hydrogel plays a significant role.
[0153] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite hydrogel with photothermal effect, characterized in that: The composite hydrogel is a skin-core structure, comprising natural bacterial cellulose and photothermal water gel; wherein the natural bacterial cellulose is the core layer, and the photothermal water gel is the skin layer.
2. The composite hydrogel with photothermal effect according to claim 1, characterized in that: The natural bacterial cellulose is in a swelling equilibrium state.
3. The composite hydrogel with photothermal effect according to claim 1, characterized in that: The thickness of the natural bacterial cellulose and the photothermal water gel are both 1 to 10 mm, preferably 3 mm.
4. The composite hydrogel with photothermal effect according to claim 1, characterized in that: The photothermal water gel comprises polydopamine, polyvinyl alcohol and water; wherein the water content of the photothermal water gel is 87.5-95wt%; the mass fraction of the polyvinyl alcohol in the photothermal water gel is 5-12.5wt%; and the polydopamine is prepared by oxidation of dopamine hydrochloride under alkaline conditions.
5. The composite hydrogel with photothermal effect according to claim 1, characterized in that: The photothermal water gel comprises bacterial cellulose, bamboo charcoal and water, wherein the mass volume ratio of the bacterial cellulose to water is 15 g / L to 30 g / L, and the mass volume ratio of the bamboo charcoal to water is 0.5 g / L to 1 g / L.
6. The method for preparing a composite hydrogel with photothermal effect according to any one of claims 1 to 4, characterized in that: The steps include: S11: placing natural bacterial cellulose in deionized water to reach swelling equilibrium, cutting it into a predetermined shape, and placing it at the center of the bottom of the mold; S12: Weigh dopamine hydrochloride and dissolve it in deionized water, adjust the pH to 8.0-8.8, and obtain a polydopamine solution; weigh polyvinyl alcohol powder and add it to the polydopamine solution, mix well, and adjust the pH to neutral to obtain a photothermal water gel solution; S13: evenly distributing the photothermal water gel solution around the natural bacterial cellulose in the mold of step S11, freezing it at -10 to -80°C for 8 to 12 hours, and then melting it to obtain a composite hydrogel.
7. The method for preparing a composite hydrogel with photothermal effect according to claim 6, characterized in that: The concentration of the dopamine hydrochloride is 0.019 g / L to 0.285 g / L.
8. The method for preparing a composite hydrogel with photothermal effect according to any one of claims 1 to 3 and 5, characterized in that: The steps include: S21: placing natural bacterial cellulose in deionized water to reach swelling equilibrium, cutting it into a predetermined shape, and placing it at the center of the bottom of the mold; S22: lithium hydroxide: urea: deionized water are weighed in a weight ratio of 4.6:15:80.4 and fully dissolved to obtain a bacterial cellulose solvent; bacterial cellulose is weighed separately to make a homogenate, and dried to form a bacterial cellulose powder; the bacterial cellulose powder and bamboo charcoal are dissolved in a solvent, mixed in an ice bath, and placed in an environment of -10°C to fully dissolve to obtain a photothermal water gel solution; S23: adding glutaraldehyde to the photothermal water gel solution, mixing evenly, and then evenly arranging the solution around the natural bacterial cellulose in the mold in step S11, and leaving the solution at room temperature to obtain a composite hydrogel.
9. Use of the composite hydrogel with photothermal effect as claimed in any one of claims 1 to 5 for preparing wound dressings or drug release carriers.
Citation Information
Patent Citations
Mask with photothermal effect and preparation method thereof
CN110960470A
Double-network hydrogel shell polycystic core structure trichoderma harzianum agent
CN112111412A
Preparation of nano-crystalline cellulose aerogel material with high strength and high adsorption performance
CN112126108A
Preparation method of regenerated bacterial cellulose composite hydrogel dressing
CN113069590A
Alginate encapsulated bacterial cellulose composite photo-thermal antibacterial medical dressing and preparation method thereof
CN114000349A